THE EFFECT OF OVAPRIM INJECTION AND OXYTOSIN HORMONE WITH DIFFERENT DOSAGE TO OVULATION AND HATCHING RATE OF NILEM FISH (Osteochilus hasselti) - Setianingrum, Dwi Rezno; Nuraini, Nuraini; Sukendi, Sukendi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
ABSTRACT This research was conducted in August-November 2019 at the Hatchery  and fish breeding Laboratory, Faculty of Fisheries and Marine, Riau University. The purpose of this study was to study the injection of ovaprim and the hormone oxytocin with different doses of ovulation and hatchability of Nilem fish (Osteochilus hasselti). The method used in this study is an experimental method using a completely randomized design with 5 levels of treatment and 3 replications. The treatments in this study were: O100% (100% Ovaprim), O75% + OK25% (75% Ovaprim + 25% Oxytocin), O50% + OK50% (50% Ovaprim + 50% Oxytocin), O25% + OK75% ( 25% Ovaprim + 75% Oxytocin), OK100% (100% Oxytocin). The best treatment is in the treatment of O50% + OK 50% (50% Ovaprim 50% Oxytocin) with a latent time of 5 hours 10 minutes, ∑ THS 189 eggs / g, IOS 10,63%, increase in egg diameter 0,1 mm, increase in egg maturity 78,79%. FR value 87.59%, HR 89.06%, and SR on the 5th day was 78.79%. Water quality measurements range from: temperature 26-280C, DO 2.9-6.4 ppm, and pH 6-7.Keywords :Osteochilus hasselti, Ovaprim, Oxytocin, Ovulation, Hatching rate